Investigation of stability and activity of quaternized zinc phthalocyanine photosensitizer with fused extended conjugation in vitro conditions - Karahan, Yesim; Kose, Guelsah Gumrukcu; Karaoglan, Guelnur K. E. S. E. R.; Sakar, Dolunay (YILDIZ TECHNICAL UNIV, 2024)
Quaternized zinc phthalocyanine (QZnPc) which is water soluable is a promising candidate for photo dynamic therapy (PDT) applications. The physicochemical properties like the stability, activity, particle size, surface charge of tetrakis-(4-[(1E)-3-iminoprop-1-en-1-yl]N,N,N-trimethylphenylammonium) phthalocyaninato zinc(II)] tetraiodide (II) quaternized zinc phthalocyanine (fused extended conjugation, QZnPc-FE) were investigated. The Zeta Potential Analyzer was used for this purpose. QZnPc-FE is freshly synthesized, water soluble quaternized zinc phthalocyanine and used as potential photosensitizer for PDT application. The stability and activity behavior of QZnPc-FE was determined in vitro conditions such as different pHs and in simulated body fluids as function of time via Zetasizer measurements and UV/VIS absorbances, respectively. Morphology of the QZnPc-FE was determined via XRD and the organic solvent effect with different polarity on QZnPc-FE was checked by UV/VIS. The optimum stability and activity conditions of QZnPc-FE in vitro conditions were determined, and the obtained results showed that the studied compound can be used for medical (PDT) and pharmaceutical applications.
Keywords: Water Soluable Quaternized Zinc Phthalocyanine; Zeta Potential; Particle Size; Stability; Particle Charge; Activity; Engineering